Research for WSN routing algorithm based on novel multi-level minimal dominating clustering - LUO Guang-chun; LI Jiong (Tongxin xuebao)
The novel mult-level minimal dominating clustering arithmetic is the reprove of the random clustering arith-metic,we discussed the arithmetic of minimal dominating set,and developed a improved predigestion arithmetic of near minimal dominating set,reduced the workload of compute the minimal dominating set.After discussed the realize of minimal dominating for WSN.The test results validate the improve in the energy consumption.